2022
DOI: 10.2337/dci22-0014
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure: An Underappreciated Complication of Diabetes. A Consensus Report of the American Diabetes Association

Abstract: Heart failure (HF) has been recognized as a common complication of diabetes, with a prevalence of up to 22% in individuals with diabetes and increasing incidence rates. Data also suggest that HF may develop in individuals with diabetes even in the absence of hypertension, coronary heart disease, or valvular heart disease and, as such, represents a major cardiovascular complication in this vulnerable population; HF may also be the first presentation of cardiovascular disease in many individuals with diabetes. G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(147 citation statements)
references
References 219 publications
3
135
0
9
Order By: Relevance
“…These findings suggest that patients in this group have hyperlipidemia, which is a risk factor for cardiovascular disease. In addition to hyperglycemia, an increase in the incidence of cardiovascular disease (CVD) among patients with T2DM has led to a greater recognition of hypertension and hyperlipidemia as important targets of therapy [30]. Clinical studies in T2DM patients have revealed that lowering cholesterol and maintaining tight blood pressure management lowers the risk of significant cardiovascular events [31,32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that patients in this group have hyperlipidemia, which is a risk factor for cardiovascular disease. In addition to hyperglycemia, an increase in the incidence of cardiovascular disease (CVD) among patients with T2DM has led to a greater recognition of hypertension and hyperlipidemia as important targets of therapy [30]. Clinical studies in T2DM patients have revealed that lowering cholesterol and maintaining tight blood pressure management lowers the risk of significant cardiovascular events [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…A case control study that included (100) patients and (35) healthy controls were all included in this study. Patients (43 males, 57 females) were separated into three groups: (35) type 2 diabetes mellitus (14 males, 21 females), (30) hypertension (12 males, 18 females), and (35) type 2 diabetes mellitus with hypertension (17 males, 18 females). Participants in the control group (20 males, 15 females) were matched by the age, weight, and had no disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence rates of abnormal clinical biomarker levels based on ADA guidelines were reported (cut-off levels defined as NTpBNP > 125 pg/mL or hs-TnT > 12.5 pg/mL [latter based on manufacturer’s recommendation of the 99 th percentile for the assay]) [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The STOP-HF study used a strategy of BNP-guided management to institute preventative therapies and screening with echocardiography to further assess subclinical LVD [ 5 ]. Based on this and other published papers on the utility of measuring clinical biomarkers to assess risk of future HF [ 6 9 ], the recent American Diabetes Association (ADA) guidelines suggest measuring NTpBNP and hs-TnT in all patients without a history of clinical HF to delineate the need for cardiac imaging [ 10 ]. This study aimed to examine the utility of risk scores (ARIC-HF and WATCH-DM) and clinical biomarkers (NTpBNP and hs-TnT) in detecting subclinical LVD or structural heart disease (SHD) in community-based populations with T2DM thus identifying those with stage B HF and at risk of progression to symptomatic HF.…”
Section: Introductionmentioning
confidence: 99%